The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1097/cej.0b013e32833233be
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cancer mortality in Brazil, 1980–2004

Abstract: Scanty information, limited to selected areas of the country, is available on cancer mortality in Brazil. Age-standardized (world population) mortality rates between 1980 and 2004, derived from the WHO database, were computed for all cancers and 24 major cancer sites in Brazil. Joinpoint regression analyses were used to identify the significant changes in trends and estimate annual percent change (APC) in rates. Total cancer mortality rates increased over the last decade in men (APC = 0.5) to reach 101.2/100 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
(43 reference statements)
5
36
0
3
Order By: Relevance
“…Other authors, however, had reported a stabilizing of rates in the period 1966-1991 22 . Moreover, the increased rates in the later 1990s in Argentina are consistent with trends in other Latin American countries such as Brazil 23 , Chile 24 and Mexico 21 .…”
Section: Discussionsupporting
confidence: 66%
“…Other authors, however, had reported a stabilizing of rates in the period 1966-1991 22 . Moreover, the increased rates in the later 1990s in Argentina are consistent with trends in other Latin American countries such as Brazil 23 , Chile 24 and Mexico 21 .…”
Section: Discussionsupporting
confidence: 66%
“…The present study confi rms other recent research, 6 showing that the magnitude of the cancer mortality rates in Brazil is, in general, lower than that of developed countries. Nonetheless, the overall trends and the trends for the leading sites do not indicate reduction, except for stomach and cervical cancer which, despite being on the decline, can be considered high in relation to the trends found in other countries.…”
Section: Discussionsupporting
confidence: 75%
“…The trend of standardized mortality rates was assessed by polynomial regression, considering the rates standardized according to world population (6) mortality from stomach cancer, according to sex, and stratified by Brazilian regions (Midwest, Northeast, North, Southeast, and South).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the best evidence for the study of the magnitude of the problem in Brazil is the study of mortality in the country (6) . Thus, this study aims to assess the trend of mortality from stomach cancer in Brazil according to regions between 1980 and 2009.…”
mentioning
confidence: 99%